Effects of Population Age on the Annual Net Primary Productivity and Seed Yield of Artificial Grasslands on the Eastern Qinghai-Tibetan Plateau - Li, Cong; Ren, Yanmei; Wu, Lin; Wang, Xinchuan; Liang, Defei; Zhou, Huakun; Ma, Zhen; Zhang, Chunhui (Frontiers in Environmental Science, 2022)
The forage yield and quality of artificial grasslands typically decline rapidly over time after planting. Moreover, the reason for this decline of artificial grassland remains unclear. Here, we evaluated the relationship between years since planting and annual net primary productivity (ANPP), seed yield, and reproductive allocation (ie., the ratio of seed yield to annual net primary productivity) for eight common gramineous species separately planted in monoculture artificial grasslands in the Qinghai-Tibetan Plateau. We utilized T50 values (the time when ANPP or seed yield drop to 50% of their maximum values) to quantify the decline rates of eight artificial grasslands respectively, and additionally evaluated the influence of evolutionary history and other plant attributes on T50 (ANPP) and T50 (seed yield). We found that both ANPP and seed yield decreased linearly over time following planting for all species. ANPP generally declined more rapidly than did seed yield. The reproductive allocation of Deschampsia cespitosa, Festuca kirilowii, Festuca kryloviana, and Festuca sinensis increased significantly over time after planting. We did not observe any association of evolutionary history, seed mass, plant height, reproductive allocation, ANPP (second year), seed yield (second year) with T50 (ANPP) and T50 (seed yield). In addition, clonal propagation mode may influence declines of artificial grassland, and evolutionary history may shape shifts in reproductive allocation with plant population aging. This study was the first to utilize T50 values for the study of artificial grassland declines. Our research framework thus has the potential to guide future quantitative studies of artificial grassland declines.